Fast 3D Printing with Chitosan/Polyvinyl alcohol/Graphene Oxide Multifunctional Hydrogel Ink that has UltraStretch Properity. Issue 10 (9th March 2022) - Hao, Feiyue; Maimaitiyiming, Xieraili
Abstract: Chitosan(CS) hydrogels prepare under novel alkaline conditions have attracted attention because they have more excellent mechanical properties than traditional acidic preparation conditions.We observe that the prepared CS sol still exhibits excellent printability even in the lower mass fraction range.It can be empolyed for fast printing and stable shape retention at room temperature.In order to meet the 3D printing of hydrogels with high mechanical properties, a solid cross‐linked network is constructed based on polyvinyl alcohol (PVA) and CS .The hybrid hydrogel ink retains the excellent printability of CS hydrogel while also enhancing its mechanical properties (strain>400 %).Then graphene oxide (GO) is introduced into the system to give full play to the multi‐functional characteristics of the composite hydrogels.This kind of hydrogel is used to print flexible sensors and shows very distinctive application value.Furthermore, it can be served as a flexible electrode material for the design of complex circuit systems, contributing to the development of flexible sensors.In short, this work will open a new research path for the application of fast 3D printing hydrogels with ultrastrenth properity. Abstract : Benefit from excellent printability, high mechanical properties and wide temperature response range, the composite multifunctional hydrogel ink base on CS/PVA/GO can be used not only to design flexible circuits, but also to make temperature‐adjustable smart switches.Beside, It is also possible to manufacture temperature and humidity sensors with a longer service life.In summary, it provides a promising material for flexible electronics.